Про «особистісність» та «організаційність» немайнових прав учасників господарських товариств - Жорнокуй, В.; Zhornokui, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуті питання з’ясування правової природи та характеристики немайнових корпоративних прав. Запропоновано розмежовувати цивільні відносини за особистісним критерієм – на особисті та неособисті; за майновим критерієм – на майнові і немайнові. Існує потреба у виділенні в окрему групу цивільних відносин немайнових корпоративних відносин, зміст яких становлять немайнові права учасників господарських товариств. При цьому учасник не володіє «особистими немайновими правами», а для позначення групи прав, які йому належать нарівні з майновими, коректно вживати поняття «немайнові права». The paper deals with the determination of the legal nature and characteristic features of the intangible corporate rights. It is suggested to distinguish between the civil relations using two types of criteria: according to the personal criteria these relations may be personal and non-personal; by property criterion – proprietary relationships and non-proprietary ones. There is a need to separate a specific group of civil relations regarding corporate relations, the content of which is determined by non-proprietary rights of the participants of business entities. The analysis suggests the following: 1) the participant (shareholder) does not possess personal «non-property rights»; 2) to designate a group of rights that he (shareholder) owns on a par with proprietary rights, it is correct to use the concept/term of «non-proprietary rights», because the civil legal doctrine interprets the personal non-proprietary rights as inalienable, absolute rights which do not imply any property content and are inseparably associated with an individual - the bearer of these rights.
On the «Personal» and «Corporate» Non-Property Rights of the Participants of Business Entities.
Keywords: господарське товариство; права учасників; учасник товариства; акціонер; немайнові корпоративні права; business entities; rights of the participants; a member of the company; shareholder; nonproprietary corporate rights